Analysis of the permeability evolution law of in situ steam pyrolysis of bituminous coal combing with in situ CT technology. (15th January 2023) - Shi, Jianhang; Feng, Zengchao; Zhou, Dong; Li, Xuecheng; Meng, Qiaorong
Abstract: The permeability evolution of bituminous coal under in situ steam pyrolysis was studied combing with in situ CT technology. The results showed that: 1) Permeability varied negatively logarithm with pore pressure, which is related to adsorption expansion; 2) Permeability changed in a "V" shape with temperature. In a range of 300–400 °C, the coal sample continues to soften under hydrothermal action, the external stress closed the crack, and permeability decayed; 3) At 400–600 °C, the hydrothermal action promoted the pyrolysis of the coal samples and generated more seepage channels. The continuous compression by the external stress on the coal body suppressed the expansion of the pores and fissures. However, the former played a leading role in promoting permeability, and permeability showed a piecewise linear growth. CT results showed that the porosity trend of the coal samples was consistent with that of permeability; 4) Above 400 °C, superheated steam promotes the pyrolysis of the coal samples and improved permeability due to its excellent convection and thermal conductivity, drive effect, and participation in chemical reactions. Highlights: Permeability evolution in bituminous coal under THMC was studied. The microstructure evolution of bituminous coal was studied by in situ CT technology. The weakening mechanism of bituminous coal under superheated steam was clarified.